37.3k views
1 vote
3-2(x-1)=2+4x
How do you solve

2 Answers

5 votes
You would multiply the negative two by x then the negative to by negative one then you would get 3-2x+2=2+4x then you would ad 2 x to 4x and get 6x the. Subtract 3-2 and you would get 1 the. You would subtract the 2 from the 1 and get -1 and you would get -1=6x so you would divide 6x and 1 and you would get x=-1/6 ( hope this helps)
User Julien Kronegg
by
5.7k points
3 votes

Answer:

x = 1/2

Explanation:

3 - 2(x - 1) = 2 + 4x

3 - 2x + 2 = 2 + 4x

-2x + 5 = 2 + 4x

-2x - 4x = 2 - 5

-6x = -3

x = -3/-6

x = 1/2

User Albee
by
5.3k points